A SIX6 Nonsense Variant in Golden Retrievers with Congenital Eye Malformations - Petra Hug; Linda Anderegg; Nicole Dürig; Vincent Lepori; Vidhya Jagannathan; Bernhard Spiess; Marianne Richter; Tosso Leeb (Genes, 2019)
Causative genetic variants for more than 30 heritable eye disorders in dogs have been reported. For other clinically described eye disorders, the genetic cause is still unclear. We investigated four Golden Retriever litters segregating for highly variable congenital eye malformations. Several affected puppies had unilateral or bilateral retina dysplasia and/or optic nerve hypoplasia. The four litters shared the same father or grandfather suggesting a heritable condition with an autosomal dominant mode of inheritance. The genome of one affected dog was sequenced and compared to 601 control genomes. A heterozygous private nonsense variant, c.487C>T, was found in the SIX6 gene. This variant is predicted to truncate about a third of the open reading frame, p.(Gln163*). We genotyped all available family members and 464 unrelated Golden Retrievers. All three available cases were heterozygous. Five additional close relatives including the common sire were also heterozygous, but did not show any obvious eye phenotypes. The variant was absent from the 464 unrelated Golden Retrievers and 17 non-affected siblings of the cases. The SIX6 protein is a homeobox transcription factor with a known role in eye development. In humans and other species, SIX6 loss of function variants were reported to cause congenital eye malformations. This strongly suggests that the c.487C>T variant detected contributed to the observed eye malformations. We hypothesize that the residual amount of functional SIX6 protein likely to be expressed in heterozygous dogs is sufficient to explain the observed incomplete penetrance and the varying severity of the eye defects in the affected dogs.